An injectable self-healing CS/PDA–AgNPs hybrid hydrogel for mild and highly-efficient photothermal sterilization. (8th April 2022) - Gan, Ying; Lin, Chen; Zhu, Hao; Cheng, Xuedan; Liu, Chaoqun; Shi, Jiahua
Abstract : An injectable self-healing hybrid hydrogel was constructed for combating bacterial infection under mild photothermal conditions. Abstract : Bacterial infection remains one of the most serious and growing health issues, which leads to millions of human deaths every year. Development of an efficient photothermal sterilization platform is thus of great significance for treating bacterial infection. However, single photothermal treatment usually requires relatively high temperatures (55–65 °C) to kill bacteria, which inevitably induces damage to surrounding healthy tissues. The combination of photothermal therapy with an antibacterial agent can overcome this challenge by decreasing the photothermal temperature. Herein, an injectable and self-healing hybrid hydrogel was prepared for photothermal antisepsis at high efficiency under mild conditions. The hybrid hydrogel was prepared by self-polymerization of dopamine into a photothermal agent polydopamine and simultaneous reduction of silver ions to silver nanoparticles in a chitosan network. As expected, the obtained hybrid hydrogel exhibits good mechanical properties and self-healing ability, meaning that it can spontaneously recover after mechanical damage, maintain its integrity, and restore its original functions with a longer lifetime. Moreover, the antibacterial results indicate that the hybrid hydrogel displays commendable antimicrobial ability both in vitro and in an in vivo mice wound model under mild photothermal conditions. Besides this, no obvious toxicity was detected during the treatment process. Overall, the hybrid hydrogel may serve as a promising candidate for wound treatment in the clinic.